Prediction of irradiation embrittlement in WWER-440 Reactor Pressure Vessel materials - Brumovsky, M.; Kytka, M.; Debarberis, L.; Gillemot, F.; Kryukov, A.; Valo, M. (Вопросы атомной науки и техники, 2007)
Prediction of irradiation embrittlement of Reactor Pressure Vessel (RPV) materials is performed usually in accordance with relevant codes and standards that are based on large amount of information from surveillance and research programs. The existing Russian Code (Standard for Strength Calculations of Components and Piping in Nuclear Power Plants (NPPs) – PNAE G 7-002-86) for the WWER RPV irradiation embrittlement assessment was approved more than 20 years ago and based mostly on the experimental data obtained in research reactors with accelerated irradiation. The validation of the above Code has been made without the surveillance specimen results that were produced in 1980-1990s. Thus, new analysis of all available data was required for more precise prediction of radiation embrittlement of RPV materials. Based on the fact that large amount of data from surveillance program as well as some research programs, IAEA International Database on RPV Materials (IDRPVM) has been used for the detailed analysis radiation embrittlement of WWER RPV materials. Thus, the following activities have been performed within the IAEA Co-ordinated project: Collection of complete WWER-440 surveillance and other similarly important data into the IDRPVM, Analysis of radiation embrittlement data of WWER-440 RPV materials using IDRPVM database, Evaluation of predictive formulae depending on material chemical composition, neutron fluence and neutron flux, Development of the guidelines for prediction of radiation embrittlement of operating reactor pressure vessels of WWER-440 including methodology for evaluation of surveillance data of a specific operating unit.